Digital impact : the two secrets to online marketing success - Mayar, Vipin, 1962-; Ramsey, Geoff, 1959- (Wiley, 2011)
"Win online by attracting the right customers and getting the right performance measurement. Digital Impact answers the critical questions marketers have about connecting with and influencing consumers online. Written in an easy-to-read, approachable format, this helpful guide presents provocative content along with practical, commonsense methods that can be followed by any businessperson at companies of all sizes. The discussion hones in on two keys to success: building a performance measurement approach that will let you get maximum impact out of your online marketing and ad dollars, and creating magnetic content that attracts customers and keeps them engaged with your brand. Leverage trust and build ROI in social media and mobile spaces. Get actionable data, best practices, cases studies, anecdotes, practical coaching tips and strategic insights. Engage customers who typically resist advertising messages. Learn from authors who have extensive experience across major industries and accounts, giving them a wide business appeal. Whether your budget is corporate-sized or on a shoestring, you'll want to achieve the measurable bottom-line improvements that come with having Digital Impact."-- Vydavatelská anotace
Obsahuje rejstřík
Keywords: internetový marketing; elektronický obchod; Internet marketing; electronic commerce; příručky; handbooks, manuals, etc